The Influence of Public Elementary School Teachers' Authority on Students' Character - Dina Maharani; Azizah Hanum OK (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
Teachers are role models for students in the school environment, a teacher's personality has a huge influence on the morals of their students. The fact in the field is that there are still many teachers who do not reflect what should be an example for each of their students. This research aims to analyze the influence of teacher authority on the formation of student morals at SD Negeri 014628. This research is quantitative research using positivism methods. The data from this research were analyzed using the normality test, linearity test, and partial test or t-test formulas. The population in this study was 139 students at State Elementary School 014628, sampling in this study was carried out randomly, the sample size was 30 people. Data was collected using questionnaire and documentation techniques. From the results of partial test calculations (t-test), the value of t count is 5.767 > t table 2.048. And the significance value of the influence of variable X on variable Y is 0.001 < 0.005, which can be stated that Ho is rejected and Ha is accepted. Based on the research results, it can be concluded that there is a significant influence between teacher authority (X) on the formation of student character (Y) so that the positive values taught by teachers such as discipline, ethics and responsibility can be implemented well by students in the future.Keywords: Teacher Authority, students’ characters, elementary school